Teknologi Pangan Produk Perikanan : Fermentasi Terasi - Ropikoh, Siti; Sufyan, Moch Iqbal; Haris, Helmi (Jurnal Ilmiah Pangan Halal, 2022)
The large number of fishery commodities spread across Indonesia has great potential for the development of fish-based food products in the future. Not all fishery and marine products are used optimally even though their availability is very large in nature, for example, rebon shrimp and small fish. The weakness of fresh commodities such as fisheries requires processing so that they can be consumed in the long term because fish is a perishable food. The process of processing rebon shrimp and fish with the help of the fermentation process into shrimp paste products, so as to extend the shelf life. The purpose of this review journal is to find out the differences between shrimp and fish paste and how consumers like them to give advice to businesses or coastal communities about the potential for developing shrimp paste. The method used is Randomized Block Design to determine the quality and determinants of nutritional content and also the results of processing shrimp paste products.